Predictability of European winter 2020/2021: Influence of a mid‐winter sudden stratospheric warming. (22nd August 2022) - Lockwood, Julia F.; Stringer, Nicky; Thornton, Hazel E.; Scaife, Adam A.; Bett, Philip E.; Collier, Tamara; Comer, Ruth; Dunstone, Nick; Gordon, Margaret; Hermanson, Leon; Ineson, Sarah; Kettleborough, Jamie; et al.
Abstract: Boreal winter (December–February) 2020/2021 in the North Atlantic/European region was characterised by a negative North Atlantic Oscillation (NAO) index. Although this was captured within the ensemble spread of predictions from the Met Office Global Seasonal forecast system (GloSea5), with 17% of ensemble members predicting an NAO less than zero, the forecast ensemble mean was shifted towards a positive NAO phase. The observed monthly NAO anomalies were particularly negative in January and February, following an early January sudden stratospheric warming (SSW), and a prolonged period of Phase 6 or 7 of the Madden Julian Oscillation (MJO) in late January/early February. In contrast, predictions showed the expected teleconnection from the observed La Niña, with a positive NAO signal resulting from a weakening of the Aleutian Low leading to a reduction in tropospheric wave activity, an increase in polar vortex strength and a reduced chance of an SSW. Forecasts initialised later in the winter season successfully predicted the negative NAO in January and February once the SSW and MJO were within the medium range timescale. GloSea5 likely over‐predicted the strength of the La Niña which we estimate caused a small negative bias in the SSW probability. However, this error is smaller than the uncertainty in SSW probability from the finite forecast ensemble size, emphasising the need for large forecast ensembles. This case study also demonstrates the advantage of continuously updated lagged ensemble forecasts over a 'burst' ensemble started on a fixed date, since a change in forecast signal due to events within the season can be detected early and promptly communicated to users. Abstract : Boreal winter 2020/2021 was characterised by a negative North Atlantic Oscillation (NAO) pressure pattern, yet the signals from the ensemble mean of many seasonal forecast systems were for a positive NAO. In this letter we focus on the GloSea5 seasonal forecast system and investigate if there is any evidence for forecast error, or whether the discrepancy was more likely due to unpredictable natural variability.